Potential endophytic bacteria for increasing paddy (MR220) growth performances / Arif Muzamir Pauzi - Pauzi, Arif Muzamir (Faculty of Plantation and Agrotechnology, 2015)
Endophytic bacteria have the ability for promoting the growth performance of paddy crops. Endophytic bacteria can be used as a substitute for chemical fertilizer that could cause harmful effects towards humans, animals and environments. The use of chemical can disrupt the ecosystem balancing. Endophytic bacteria also do not have negative effects on the host plant it colonizing. It helps the growth of plants by producing the growth hormones for plant health. This study was carried out to investigate the potential of endophytic bacteria towards the growth performance of paddy crops. Further research on endophytic bacteria is needed to ensure its potential to paddy crops.